STUDY OF THE ANTICONVULSANT ACTIVITY OF ETHANOLIC EXTRACT OF ROOT OF ACORUS CALAMUS IN ALBINO RATS - Kaushik, Shipra; Gohain, Kalpana (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Root of Acorus calamus has been traditionally used as an anticonvulsant. The aim of the study is to assess the anticonvulsant activity of ethanolic extract of A. calamus (EEAC) by maximal electroshock seizure (MES) and pentylenetetrazol (PTZ)-induced seizure models on albino (Wistar strain) rats. Methods: Albino rats were taken and divided into five groups, each consisting of five rats both for MES and PTZ model. One group was used as control (normal saline 10 ml/kg), one as standard (phenytoin in MES model/diazepam in PTZ model), and three groups for the test drug (EEAC in the doses of 100, 200, and 400 mg/kg). In MES model, maximal electrical shock of 150 mA was passed for 0.2 s through earlobe electrodes after 30 min of giving the drugs and normal saline. Different stages of convulsions were noted down along with time spent by the animal in each phase of convulsions. In PTZ model, PTZ was injected 30 min after giving the drugs and normal saline, and onset of action and severity of convulsions were noted. Data were statistically analyzed by one-way analysis of variance followed by multiple Dunnett's test. Results: EEAC dose dependently reduced the duration of tonic hind limb extension in MES model, and there was increase in latency and occurrence of convulsions in PTZ model. Conclusion: EEAC has anticonvulsant activity.